PERANCANGAN FURNACE MULTIFUNGSI UNTUK GERABAH KERAMIK - Erni Junita Sinaga (Prodi Teknik Industri S1 Institut Teknologi Nasional Malang, 2011)
Craftsmen ceramics industry (home industry) are usually produced goods anddecorative ceramic pottery. In the ceramic combustion activity, the operator working positionin a state squatting causing muscle fatigue, whereas for ceramic drying process is done byusing sunlight energy. If the weather is cloudy then the drying process of ceramics can not bedone thus inhibiting production. To overcome the above constraints, so that created aburning tool and ceramic dryer at once.The method used by anthropometric measurements to produce data with severalpercentiles (5%, 50%, 95%). The data used is the long reach of his hand forward, hand gripdiameter, height and standing elbow height. Furthermore, comparing the standard time andstandard output of the old equipment with new equipment. The results obtained by theceramic combustion process is shorter, the combustion process in the old tool takes 8.07hours while the new tool takes 3.67 hours per combustion. Output standard old tools produce1.2 units per day, while the new equipment produces 2.7 units per day, so that profit a newtool showed an increase of 125%